Análise da secagem de limão tahiti (Citrus latifolia - Tanaka) em fatias e de suas frações: epicarpo, mesocarpo e endocarpo - Silva, Adriana (Universidade Federal de São Carlos, 2015)
The tahiti lemon belongs to the family Rutaceae, Citrus of the genus, species Citrus Latifolia, the variety Tanaka. It is a heterogeneous fruit, formed by three distinct fractions, them being the epicarp (outer shell), the mesocarp (white layer), and endocarp (pulp with buds and vesicles containing its juice). Both the whole lemon as its fractions have several culinary applications, and also in the food and pharmaceutical industry. Therefore dehydration of this product for food has as challenges, preserve good visual appearance and the components of interest at the end of the process. The objective of this study is to analyze the drying of each lemon fractions tahiti (epicarp, mesocarp and pulp), alone, and also of the slices at different temperatures and to evaluate color changes and shrinking occurring in the drying. Furthermore, verify the fits for the drying kinetics curves to diffusive models, empirical and semi-empirical and also test the use of ANNs for adjustment and simulation of drying. The drying tests were conducted in a natural convection oven with air at temperatures of 30°C, 40°C, 50°C, 60°C and 70°C. It was found that the epicarp and mesocarp fractions were quickly reached dynamic equilibrium moisture, followed by the endocarp, and the slices showed shorts rates of drying. Under the conditions evaluated for endocarp sliced, and the slices at 70°C there was a reduction drying time of about 90% over the time required at 30°C, and the fractions that make up the shell this reduction was approximately 66%. The fits of the drying curve to the diffusive kinetic model were reasonable. Adjustments data to empirical models in general were good, and among the tested models, models of Page and Overhults presented the best fits the drying kinetics. The ANNs showed a promising tool in the prediction and simulation of drying kinetics, but a larger number of data is needed to improve their performance. The color change occurred increasingly with increasing drying temperature, being higher for the endocarp and the slice. The shrinkage was higher in the early stages of drying, and reducing the surface area of the samples was about 33%.
Keywords: Secagem; Limão; Fenômenos de transporte; ENGENHARIAS::ENGENHARIA QUIMICA